Chronic Stability of Bipolar Epicardial Plunge Electrodes in Dogs - Brautigam, Robert T.; Porter, R. Stephen; Frasch, Fred; Kutalek, Steven P. (Journal of investigative surgery, 1991)
We constructed and surgically implanted 114 chronic bipolar epicardial plunge electrodes for programmed left ventricular stimulation in closed chest dogs; 88 electrodes could be analyzed in animals surviving infarct surgery. Electrode plunges were constructed of silver wire, with conduction strands of silverplated copper wire, in medical grade silicone tubing. Electrodes were implanted epicardially through left thoracotomy and secured with prolene. Wires exited the fifth intercostal space and were tunneled subcutaneously and secured at the dorsal aspect of the neck. Baseline thresholds (mA) were recorded at a paced cycle length of 300 ms and pulse duration of 1 ms. At least 5 days after implantation, under light Nembutal sedation, thresholds were reassessed before programmed stimulation. Each lead was tested repeatedly over 5-177 (mean 28) days. The number of leads decreased with time due to animal attrition from ventricular arrhythmias. Mean pacing threshold at implantation was 0.25 mA. Mean and median threshold values reached plateau after 1 week and showed little change thereafter for the duration of the study. More than 50% of the leads maintained thresholds less than 1.5 mA through the entire study. In animals that survived, 86% of the electrodes remained useful for the duration of the protocol. These data support the use of this electrode system as effective and reliable for chronic electrophysiologic studies in dogs